PENGARUH MODEL PEMBELAJARAN PBL (PROBLEM BASED LEARNING) TERHADAP HASIL BELAJAR MATEMATIKA PADA SISWA KELAS 4 SEKOLAH DASAR - Maharani, Arifatun Rully; Galuh Kartika Dewi; Satrio Wibowo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the effect of the PBL (Problem – Based Learning) learning model on Grade 4 elementary school Mathematics learning outcomes and student responses after using the PBL learning model. This type of research is experimental research using a pretest-posttest control group design. The population in this study was 60 grade 4 students of SDN Sugihwaras who were divided into two groups, namely group A as the control class and group B as the experimental class, each consisting of 30 students. The result showed that the average pretest and posttest score of the control class were 61,08 and 65, while those of the experimental class were 72,5 and 82,9. The learning outcomes test shows t-count 5,55 > t-critical 2,001, indicating that the application of the PBL learning model has a significant effect on improving the learning outcomes of grade 4 students’ mathematics, and therefore, Ho can be rejected. The results of student responses provide an assessment with an average value of 77,6%, so the PBL learning model is categorized as good.